2007
DOI: 10.1016/j.ygcen.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hormone genes and osmoregulation in homing chum salmon: A minireview

Abstract: Pacific salmon migrate from ocean through the natal river for spawning. Information on expression of genes encoding osmoregulatory hormones and migratory behavior is important for understanding of molecular events that underlie osmoregulation of homing salmon. In the present article, regulation of gene expression for osmoregulatory hormones in pre-spawning salmon was briefly reviewed with special reference to neurohypophysial hormone, vasotocin (VT), and pituitary hormones, growth hormone (GH) and prolactin (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
(37 reference statements)
0
27
0
1
Order By: Relevance
“…The distance from the mouth of the Ishikari River to the Chitose Field Station is about 70 km. Analyses of data loggers attached to homing adults in the Ishikari Bay showed that fish spent a few weeks to reach the hatchery from the mouth of the Ishikari River (Kitahashi et al, 2000;Makino et al, 2007).…”
Section: Homing Chum Salmonmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance from the mouth of the Ishikari River to the Chitose Field Station is about 70 km. Analyses of data loggers attached to homing adults in the Ishikari Bay showed that fish spent a few weeks to reach the hatchery from the mouth of the Ishikari River (Kitahashi et al, 2000;Makino et al, 2007).…”
Section: Homing Chum Salmonmentioning
confidence: 99%
“…Elevated levels of sex steroid hormones have been found to be associated with the adaptation to FW in pre-spawning chum salmon (Makino et al, 2007). Makino et al found that the plasma levels of T and/or E2 were related to the amount of time spent in FW, when spontaneous behavior of pre-spawning chum salmon was monitored in an aquarium that allowed fish to migrate between separated SW and FW streams (Makino et al, 2007). An application of T, 11KT or E2 directly modulated prolactin (PRL) gene expression, a FW adaptation hormone (Hirano et al, 1987), in primary pituitary cells of pre-spawning and mature masu salmon .…”
Section: Activity Of the Pg Axis During The Spawning Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of the hypothalmus-pituitary-inter renal axis produces an increase in plasma cortisol concentrations, along with changes in other compounds associated with FW entry (Clarke and Hirano 1995;McCormick 2001;Mancera and Fuentes 2006;Norris and Hobbs 2006;Makino et al 2007). Included among the physiological responses are a shift in the number, distribution, and function of gill chloride cells (Uchida et al 1997) and the downregulation of gill Na*,K^ ATPase activity (Shrimpton et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…GTH plasma levels also increase during upstream migration in pre-spawning chum salmon (Ueda et al 1984;Kitahashi et al 1998), pink salmon (Dye et al 1986), and sockeye salmon (Truscott et al 1986), although it should be noted that these studies mainly detected LH because antiserum that distinguishes FSH from LH was not used. Makino et al (2007) reported that elevated levels of sex steroid hormones, such as E 2 , are associated with FW adaptation in pre-spawning chum salmon, and the application of sex steroid hormones has been shown to directly modulate the PRL gene during FW acclimation in adult chum salmon (Hirano et al 1987;Onuma et al 2005). Therefore, it is likely that the endocrine systems that govern salt and water homeostasis metabolism in homing salmon are regulated by PG axis activity.…”
Section: Marine and Freshwater Behaviour And Physiology 405mentioning
confidence: 99%